Efficient corrosion inhibition metal preservative and preparation method thereof

By using core-shell microspheres with crosslinked starch gel as the core core and modified silica cladding as the shell in metal preservatives, the problem of gradually weakening the corrosion inhibition effect of existing metal preservatives is solved, and efficient and long-lasting metal anticorrosion effect is achieved.

CN119824423APending Publication Date: 2025-04-15QINGDAO KUNJI NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510202597.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Under the influence of ambient temperature and humidity, ultraviolet light, its own volatility and chemical stability, the corrosion inhibition effect of existing composite metal preservatives gradually weakens, and cannot continuously provide anti-corrosion performance, resulting in metal corrosion.

Method used

Core-shell microspheres with crosslinked starch gel as the core and modified silica coating as the shell are used, combined with the preservative base material to form a high-efficiency corrosion-inhibiting metal preservative. The core-shell microspheres disintegrate when the membrane cracks, release cross-linked starch gel, absorb moisture and expand and block the cracks, maintaining the anti-corrosion effect.

Benefits of technology

Through the disintegration of core-shell microspheres and the hygroscopic expansion of cross-linked starch gel, cracks are effectively blocked, the corrosion inhibition effect of the preservative is extended, and the corrosion resistance of the metal surface is ensured for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824423A_ABST
    Figure CN119824423A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient corrosion inhibition metal preservative and a preparation method thereof, and belongs to the technical field of metal corrosion prevention, the metal preservative is composed of a preservative base material and core-shell microspheres dispersed in the preservative base material, and the core-shell microspheres are prepared by taking crosslinked starch gel as a core and taking the crosslinked starch gel as a core. The core-shell structure takes the modified silicon dioxide coating layer as a shell, and the thickness of the modified silicon dioxide coating layer is 70-86 nm. The core-shell microspheres with specific shell thickness are added into the preservative and can be disintegrated along with cracks when the cracks appear in a film layer formed by the metal preservative, so that internal crosslinked starch gel is released, the crosslinked starch gel absorbs moisture, expands and blocks the cracks, oxygen and moisture in the environment are prevented from directly contacting with metal as much as possible, and the corrosion resistance of the metal preservative is improved. The efficient corrosion inhibition effect is continuously kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal corrosion protection, and in particular to a high-efficiency corrosion-inhibiting metal corrosion inhibitor and a preparation method thereof. Background Art

[0002] Metal corrosion refers to the destruction or deterioration caused by chemical or electrochemical reactions between metal and the surrounding environment (medium). This reaction can lead to the loss or destruction of the performance of metal materials, which in turn leads to economic losses, safety hazards, environmental pollution, waste of resources and other hazards. Therefore, it is very important to strengthen the protection and control of metal corrosion. At present, people have used various methods to protect metals from corrosion, among which coating metal preservatives is one of the main methods to prevent metal corrosion.

[0003] At present, common metal preservatives mainly include inorganic metal preservatives, organic metal preservatives, composite metal preservatives and other types. Among them, composite metal preservatives have excellent weather resistance, aging resistance and corrosion resistance, and have been widely used, especially for metal structures that need to be exposed to outdoor or harsh environments for a long time.

[0004] However, most composite metal preservatives currently on the market have a common defect, namely: after the preservative is applied, the anti-corrosion effect is good in a short period of time, but as time goes by, under the influence of environmental temperature and humidity, light ultraviolet rays, and its own volatility and chemical stability, the corrosion inhibition effect of the preservative becomes poor and can no longer provide corrosion inhibition performance, causing the internal metal to corrode. Summary of the invention

[0005] The purpose of the present invention is to provide a high-efficiency corrosion-inhibiting metal preservative and a preparation method thereof, which solves the problem that the existing metal preservatives have a good corrosion-inhibiting effect in a short period of time, but as time goes by, under the influence of environmental temperature and humidity, light ultraviolet rays, and their own volatility and chemical stability, the corrosion-inhibiting effect of the preservative becomes poor, and the corrosion-inhibiting performance can no longer be provided, causing the internal metal to be corroded.

[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0007] A highly efficient corrosion-inhibiting metal preservative, the metal preservative comprising a preservative base material and core-shell microspheres dispersed in the preservative base material, wherein the core-shell microspheres are a core-shell structure with a cross-linked starch gel as a core and a modified silicon dioxide coating layer as an outer shell, and the thickness of the modified silicon dioxide coating layer is 70-86 nm;

[0008] The core-shell microspheres are used to disintegrate along with cracks when cracks appear in the film layer formed by the metal preservative, so as to release the internal cross-linked starch gel, so that the cross-linked starch gel absorbs moisture and expands to seal the cracks.

[0009] A further improvement is that, in parts by weight, the components of the preservative base material include:

[0010] Component A: 50-60 parts of bisphenol A epoxy resin, 5-10 parts of phenyl glycidyl ether, 2-10 parts of talc, 2-10 parts of alumina powder, 0.5-2 parts of sodium dodecyl sulfonate, and 0.5-1.5 parts of polydimethylsiloxane;

[0011] Component B: 20-30 parts of polyamide curing agent and 4-8 parts of propylene oxide butyl ether.

[0012] A further improvement is that the volume proportion of the core-shell microspheres in the metal preservative is 28-32%.

[0013] A further improvement is that the cross-linked starch gel is made from high-amylose corn starch after being cross-linked and modified by sodium trimetaphosphate.

[0014] A further improvement is that the modified silica coating layer is obtained by surface modification of core-shell microspheres by isobutyltriethoxysilane.

[0015] A further improvement is that the thickness of the modified silicon dioxide coating layer is 76-80 nm.

[0016] The present invention also provides a method for preparing the highly efficient corrosion-inhibiting metal preservative, the steps comprising:

[0017] S1. Prepare preservative base material for standby use;

[0018] S2, preparing cross-linked starch granules for later use;

[0019] S3, according to the dosage ratio of 1g cross-linked starch particles: 80-100mL anhydrous ethanol, the cross-linked starch particles are dispersed in anhydrous ethanol, and an ultrasonic treatment is performed with a power of 180-220W for 15-18min to obtain a dispersed system, ammonia water is added to the system to adjust the pH to 10-11, and then ethyl orthosilicate is slowly added dropwise according to the dosage ratio of 1g cross-linked starch particles: 2-3mL ethyl silicate, and the reaction is stirred at a constant temperature of 40-45°C for 6-12h, and then the pH is adjusted to 7, centrifuged and the precipitated product is collected, and the product is washed alternately with ethanol and deionized water for 3-4 times, and then the product is vacuum dried at 50-60°C for 18-24h to obtain a coating body of a cross-linked starch gel coated with silica;

[0020] S4, taking the coating body, and using isobutyltriethoxysilane to modify its surface to obtain core-shell microspheres with cross-linked starch gel as the core and modified silica coating layer as the shell;

[0021] S5. Take the core-shell microspheres and the preservative base material and mix them evenly according to a certain proportion to obtain the highly efficient corrosion-inhibiting metal preservative.

[0022] A further improvement is that the specific operation of step S1 is:

[0023] Take bisphenol A epoxy resin and phenyl glycidyl ether and add them to a reaction kettle, stir at 500-800 rpm for 8-12 minutes to form a premixed liquid, add sodium dodecyl sulfate to the premixed liquid, continue stirring for 3-5 minutes, then slowly add talcum powder and alumina powder, and heat to 45-55° C., maintain stirring for 25-35 minutes, then add polydimethylsiloxane, stir for 4-8 minutes to obtain a mixture, and finally grind the mixture with a sand mill to a fineness of ≤50nm to obtain component A;

[0024] The polyamide curing agent and propylene oxide butyl ether are mixed, and stirred at 300-500 rpm for 15-20 minutes until homogeneous, to obtain component B.

[0025] A further improvement is that the specific operation of step S2 is as follows: high-amylose corn starch is dispersed in deionized water at a dosage ratio of 5-10 g high-amylose corn starch: 100 mL deionized water, stirred in a water bath at 80-85° C. for 30-40 min to form a transparent starch paste, and then sodium trimetaphosphate accounting for 3-8% of the mass of the starch is added thereto, the pH is adjusted to 9-11 with a NaOH solution, the temperature is raised to 50-60° C., and the reaction is stirred for 2-4 h to form a cross-linked starch gel, and after the reaction solution is cooled, the supernatant is discarded by centrifugation, and then washed with deionized water 3-4 times, and vacuum dried at 50-60° C. for 10-15 h to obtain cross-linked starch granules.

[0026] A further improvement is that the specific operation of step S4 is: adding isobutyltriethoxysilane to an ethanol solution with a mass of 15-20 times and a volume concentration of 90%, then dropping acetic acid to adjust the pH to 4-5, stirring thoroughly to obtain a treatment liquid, then adding the coating body to the treatment liquid, controlling the mass ratio of the coating body to isobutyltriethoxysilane to be 5-10:1, then introducing nitrogen protection, stirring at a constant temperature of 50-60°C for 6-12h, cooling to room temperature, adding excess ethanol to dilute, and finally centrifuging to collect the particles, and washing them alternately with ethanol and deionized water for 3-4 times, and vacuum drying at 55-60°C for 12-15h, so as to obtain core-shell microspheres with a cross-linked starch gel as the core and a modified silica coating layer as the shell.

[0027] The beneficial effects of the present invention are:

[0028] (1) In the present invention, core-shell microspheres with a specific shell thickness are added to the preservative, which can disintegrate along with the cracks when cracks appear in the film layer formed by the metal preservative to release the internal cross-linked starch gel, so that the cross-linked starch gel absorbs moisture and expands to seal the cracks, thereby preventing oxygen and moisture in the environment from directly contacting the metal as much as possible, and continuing to maintain a high-efficiency corrosion inhibition effect.

[0029] (2) In the specific implementation of the present invention, by strictly selecting the thickness of the silica coating layer of the core-shell microspheres, the core-shell microspheres will not be broken during the production and daily protection process after film formation, thereby ensuring the mechanical strength of the microspheres and the stability of the film layer. When cracks appear in the film layer, the surface modification step is carried out to fully bond the core-shell microspheres to the film layer, so that the core-shell microspheres can be smoothly disintegrated with the stress of the cracks, so that the cracks pass through the core-shell microspheres as much as possible instead of directly bypassing them. In this way, enough disintegrated core-shell microspheres appear in the cracks to ensure the blocking effect. At the same time, it helps to reduce the doping amount of the core-shell microspheres, so that the daily corrosion inhibition effect can be guaranteed.

[0030] (3) In the specific implementation of the present invention, the core-shell microspheres have cross-linked starch gel as the core, which is modified by cross-linking to form a stable three-dimensional network structure, which can enhance the hygroscopic expansion effect, and is not easy to shrink after expansion, and always maintains the blocking effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the SEM morphology of the highly efficient corrosion-inhibiting metal preservative of the present invention. DETAILED DESCRIPTION

[0032] The present application is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technical personnel in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0033] 1. Main raw materials:

[0034] Bisphenol A epoxy resin: E-03 type, purchased from Hubei Yongkuo Technology Co., Ltd.;

[0035] Phenyl glycidyl ether: D-690 type, purchased from Zhongshan Yuanda New Materials Co., Ltd.;

[0036] Talc powder and alumina powder: purchased from Erping Mineral Products Processing Plant in Lingshou County;

[0037] Sodium dodecyl sulfate: purchased from Jinan Chuanxi Chemical Co., Ltd.

[0038] Polydimethylsiloxane: viscosity 350 mPa·s, purchased from Jinan Xinglongda Chemical Co., Ltd.;

[0039] Polyamide curing agent: 115 polyamide, purchased from Guangdong Suntech New Materials Co., Ltd.;

[0040] Propylene oxide butyl ether: purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.;

[0041] High amylose corn starch: the amylose content is about 72%, purchased from Shandong Jurong Bioengineering Co., Ltd.

[0042] 2. Specific Implementation of Experiments

[0043] Example 1

[0044] A highly efficient corrosion-inhibiting metal preservative, the metal preservative comprising a preservative base material and core-shell microspheres dispersed in the preservative base material, wherein the core-shell microspheres are a core-shell structure with a cross-linked starch gel as a core and a modified silicon dioxide coating layer as an outer shell;

[0045] Wherein, in terms of weight, the components of the preservative base material include:

[0046] Component A: 50 parts of bisphenol A epoxy resin, 10 parts of phenyl glycidyl ether, 2 parts of talc, 10 parts of alumina powder, 0.5 parts of sodium dodecyl sulfate, and 0.5 parts of polydimethylsiloxane;

[0047] Component B: 20 ​​parts of polyamide curing agent and 8 parts of propylene oxide butyl ether.

[0048] The preparation method of the high-efficiency corrosion-inhibiting metal preservative comprises the following steps:

[0049] S1. Take bisphenol A epoxy resin and phenyl glycidyl ether and add them to the reactor, stir at 500 rpm for 12 minutes to form a premixed liquid, add sodium dodecyl sulfate to the premixed liquid, continue stirring for 3 minutes, then slowly add talcum powder and alumina powder, and heat to 45°C, maintain stirring for 35 minutes, then add polydimethylsiloxane, stir for 4 minutes to obtain a mixture, and finally grind the mixture with a sand mill to a fineness of ≤50nm to obtain component A; mix the polyamide curing agent with propylene oxide butyl ether, stir at 300 rpm for 20 minutes until homogeneous, to obtain component B.

[0050] S2. Disperse high-amylose corn starch in deionized water at a ratio of 5 g high-amylose corn starch to 100 mL deionized water, stir in a water bath at 80° C. for 40 min to form a transparent starch paste, add sodium trimetaphosphate accounting for 3% of the starch mass, adjust the pH to 9 with NaOH solution, heat to 50° C., stir and react for 4 h to form a cross-linked starch gel, and after the reaction solution is cooled, centrifuge and discard the supernatant, wash three times with deionized water, and vacuum dry at 50° C. for 15 h to obtain cross-linked starch granules.

[0051] S3. Disperse the cross-linked starch granules in anhydrous ethanol at a ratio of 1 g of cross-linked starch granules to 80 mL of anhydrous ethanol, perform ultrasonic treatment at a power of 180 W for 18 min to obtain a dispersed system, add aqueous ammonia to the system to adjust the pH to 10, then slowly drop ethyl orthosilicate at a ratio of 1 g of cross-linked starch granules to 2 mL of ethyl silicate, react at a constant temperature of 40° C. with stirring for 6 h, then adjust the pH to 7, centrifuge and collect the precipitated product, wash the product alternately with ethanol and deionized water for 3 times, and then vacuum dry the product at 50° C. for 24 h to obtain a coating of silica-coated cross-linked starch gel.

[0052] S4, add isobutyl triethoxysilane to an ethanol solution with a mass of 15 times and a volume concentration of 90%, then add acetic acid to adjust the pH to 4, stir well to obtain a treatment solution, then take the coating body and add it to the treatment solution, control the mass ratio of the coating body to isobutyl triethoxysilane to be 5:1, then pass nitrogen protection, stir at a constant temperature of 50°C for 12h, cool to room temperature, add excess ethanol to dilute, finally centrifuge to collect particles, and wash them alternately with ethanol and deionized water for 3 times, and vacuum dry them at 55°C for 15h, so as to obtain core-shell microspheres with cross-linked starch gel as the core and modified silica coating as the shell. Scanning electron microscopy (SEM) detection shows that the thickness of the modified silica coating is between 70-75nm.

[0053] S5. Take the core-shell microspheres and the preservative base material and mix them evenly in proportion (control the volume proportion of the core-shell microspheres in the metal preservative to be 28%) (mixed with component A here, the same below), to obtain the high-efficiency corrosion-inhibiting metal preservative.

[0054] Example 2

[0055] A highly efficient corrosion-inhibiting metal preservative, the metal preservative comprising a preservative base material and core-shell microspheres dispersed in the preservative base material, wherein the core-shell microspheres are a core-shell structure with a cross-linked starch gel as a core and a modified silicon dioxide coating layer as an outer shell.

[0056] Wherein, in terms of weight, the components of the preservative base material include:

[0057] Component A: 55 parts of bisphenol A epoxy resin, 8 parts of phenyl glycidyl ether, 6 parts of talc, 6 parts of alumina powder, 1 part of sodium dodecyl sulfate, and 1 part of polydimethylsiloxane;

[0058] Component B: 25 parts of polyamide curing agent and 6 parts of propylene oxide butyl ether.

[0059] The preparation method of the high-efficiency corrosion-inhibiting metal preservative comprises the following steps:

[0060] S1. Take bisphenol A epoxy resin and phenyl glycidyl ether and add them to the reactor, stir at 600 rpm for 10 minutes to form a premixed liquid, add sodium dodecyl sulfate to the premixed liquid, continue stirring for 4 minutes, then slowly add talcum powder and alumina powder, and heat to 50°C, maintain stirring for 30 minutes, then add polydimethylsiloxane, stir for 6 minutes to obtain a mixture, and finally grind the mixture with a sand mill to a fineness of ≤50nm to obtain component A; mix the polyamide curing agent with propylene oxide butyl ether, stir at 400 rpm for 18 minutes until homogeneous, to obtain component B.

[0061] S2. Disperse high-amylose corn starch in deionized water at a ratio of 8 g high-amylose corn starch to 100 mL deionized water, stir in a water bath at 82° C. for 35 min to form a transparent starch paste, add sodium trimetaphosphate accounting for 5% of the starch mass, adjust the pH to 10 with NaOH solution, raise the temperature to 55° C., and react with stirring for 3 h to form a cross-linked starch gel. After the reaction solution is cooled, centrifuge and discard the supernatant, wash with deionized water 3 times, and vacuum dry at 55° C. for 12 h to obtain cross-linked starch granules.

[0062] S3. Disperse the cross-linked starch granules in anhydrous ethanol at a ratio of 1 g of cross-linked starch granules to 90 mL of anhydrous ethanol, perform ultrasonic treatment at a power of 200 W for 16 min to obtain a dispersed system, add aqueous ammonia to the system to adjust the pH to 10, then slowly drop ethyl orthosilicate at a ratio of 1 g of cross-linked starch granules to 2.5 mL of ethyl silicate, react at a constant temperature of 42° C. with stirring for 9 h, then adjust the pH to 7, centrifuge and collect the precipitated product, wash the product alternately with ethanol and deionized water for 3 times, and then vacuum dry the product at 55° C. for 20 h to obtain a coating of silica-coated cross-linked starch gel.

[0063] S4, add isobutyl triethoxysilane to an ethanol solution with 18 times the mass and a volume concentration of 90%, then add acetic acid to adjust the pH to 4.5, stir well to obtain a treatment solution, then take the coating body and add it to the treatment solution, control the mass ratio of the coating body to isobutyl triethoxysilane to be 8:1, then pass nitrogen protection, stir at a constant temperature of 55°C for 8h, cool to room temperature, add excess ethanol to dilute, and finally centrifuge to collect particles, and wash them alternately with ethanol and deionized water for 3 times, and vacuum dry them at 60°C for 13h, so as to obtain core-shell microspheres with cross-linked starch gel as the core and modified silica coating as the shell. Scanning electron microscopy (SEM) detection shows that the thickness of the modified silica coating is between 76-80nm.

[0064] S5. Take the core-shell microspheres and the preservative base material and mix them evenly according to a certain proportion (control the volume proportion of the core-shell microspheres in the metal preservative to be 30%) to obtain the high-efficiency corrosion-inhibiting metal preservative.

[0065] like Figure 1 As shown, it is the SEM morphology of the high-efficiency corrosion-inhibiting metal preservative. It can be seen that core-shell microspheres are dispersed in the preservative, and the overall diameter of the core-shell microspheres ranges from several hundred nanometers. At the same time, filler talcum powder and alumina powder with smaller particle size (≤50nm) after grinding are dispersed.

[0066] Example 3

[0067] A highly efficient corrosion-inhibiting metal preservative, the metal preservative comprising a preservative base material and core-shell microspheres dispersed in the preservative base material, wherein the core-shell microspheres are a core-shell structure with a cross-linked starch gel as a core and a modified silicon dioxide coating layer as an outer shell;

[0068] Wherein, in terms of weight, the components of the preservative base material include:

[0069] Component A: 60 parts of bisphenol A epoxy resin, 5 parts of phenyl glycidyl ether, 10 parts of talc, 2 parts of alumina powder, 2 parts of sodium dodecyl sulfate, and 1.5 parts of polydimethylsiloxane;

[0070] Component B: 30 parts of polyamide curing agent and 4 parts of propylene oxide butyl ether.

[0071] The preparation method of the high-efficiency corrosion-inhibiting metal preservative comprises the following steps:

[0072] S1. Take bisphenol A epoxy resin and phenyl glycidyl ether and add them to the reactor, stir at 800 rpm for 8 minutes to form a premixed liquid, add sodium dodecyl sulfate to the premixed liquid, continue stirring for 5 minutes, then slowly add talcum powder and alumina powder, and heat to 55°C, maintain stirring for 25 minutes, then add polydimethylsiloxane, stir for 8 minutes to obtain a mixture, and finally grind the mixture with a sand mill to a fineness of ≤50nm to obtain component A; mix the polyamide curing agent with propylene oxide butyl ether, stir at 500 rpm for 15 minutes until homogeneous, to obtain component B.

[0073] S2. Disperse high-amylose corn starch in deionized water at a ratio of 10 g high-amylose corn starch to 100 mL deionized water, stir in a water bath at 85° C. for 30 min to form a transparent starch paste, add sodium trimetaphosphate accounting for 8% of the starch mass, adjust the pH to 11 with NaOH solution, heat to 60° C., stir and react for 2 h to form a cross-linked starch gel, and after the reaction solution is cooled, centrifuge and discard the supernatant, wash with deionized water 4 times, and vacuum dry at 60° C. for 10 h to obtain cross-linked starch granules.

[0074] S3. Disperse the cross-linked starch granules in anhydrous ethanol at a ratio of 1 g of cross-linked starch granules to 100 mL of anhydrous ethanol, perform ultrasonic treatment at a power of 220 W for 15 min to obtain a dispersed system, add aqueous ammonia to the system to adjust the pH to 11, then slowly drop ethyl orthosilicate at a ratio of 1 g of cross-linked starch granules to 3 mL of ethyl silicate, react at a constant temperature of 45° C. with stirring for 12 h, then adjust the pH to 7, centrifuge and collect the precipitated product, wash the product alternately with ethanol and deionized water for 4 times, and then vacuum dry the product at 60° C. for 18 h to obtain a coating of silica-coated cross-linked starch gel.

[0075] S4, add isobutyl triethoxysilane to an ethanol solution with a mass of 20 times and a volume concentration of 90%, then add acetic acid to adjust the pH to 5, stir well to obtain a treatment solution, then add the coating to the treatment solution, control the mass ratio of the coating to isobutyl triethoxysilane to be 10:1, then pass nitrogen protection, stir at a constant temperature of 60°C for 6h, cool to room temperature, add excess ethanol to dilute, finally centrifuge to collect particles, and wash alternately with ethanol and deionized water 4 times, and vacuum dry at 60°C for 12h, so as to obtain a core-shell microsphere with a cross-linked starch gel as the core and a modified silica coating as the shell. Scanning electron microscopy (SEM) detection shows that the thickness of the modified silica coating is between 82-86nm.

[0076] S5. Take the core-shell microspheres and the preservative base material and mix them evenly according to a certain proportion (control the volume proportion of the core-shell microspheres in the metal preservative to be 32%) to obtain the high-efficiency corrosion-inhibiting metal preservative.

[0077] Comparative Example 1

[0078] A highly efficient corrosion-inhibiting metal preservative, the metal preservative comprising a preservative base material and core-shell microspheres dispersed in the preservative base material, wherein the core-shell microspheres are a core-shell structure with a cross-linked starch gel as a core and a silicon dioxide coating layer as an outer shell;

[0079] Wherein, in terms of weight, the components of the preservative base material include:

[0080] Component A: 55 parts of bisphenol A epoxy resin, 8 parts of phenyl glycidyl ether, 6 parts of talc, 6 parts of alumina powder, 1 part of sodium dodecyl sulfate, and 1 part of polydimethylsiloxane;

[0081] Component B: 25 parts of polyamide curing agent and 6 parts of propylene oxide butyl ether.

[0082] The preparation method of the high-efficiency corrosion-inhibiting metal preservative comprises the following steps:

[0083] S1. Take bisphenol A epoxy resin and phenyl glycidyl ether and add them to the reactor, stir at 600 rpm for 10 minutes to form a premixed liquid, add sodium dodecyl sulfate to the premixed liquid, continue stirring for 4 minutes, then slowly add talcum powder and alumina powder, and heat to 50°C, maintain stirring for 30 minutes, then add polydimethylsiloxane, stir for 6 minutes to obtain a mixture, and finally grind the mixture with a sand mill to a fineness of ≤50nm to obtain component A; mix the polyamide curing agent with propylene oxide butyl ether, stir at 400 rpm for 18 minutes until homogeneous, to obtain component B.

[0084] S2. Disperse high-amylose corn starch in deionized water at a ratio of 8 g high-amylose corn starch to 100 mL deionized water, stir in a water bath at 82° C. for 35 min to form a transparent starch paste, add sodium trimetaphosphate accounting for 5% of the starch mass, adjust the pH to 10 with NaOH solution, raise the temperature to 55° C., and react with stirring for 3 h to form a cross-linked starch gel. After the reaction solution is cooled, centrifuge and discard the supernatant, wash with deionized water 3 times, and vacuum dry at 55° C. for 12 h to obtain cross-linked starch granules.

[0085] S3. Disperse the cross-linked starch granules in anhydrous ethanol at a ratio of 1 g of cross-linked starch granules to 90 mL of anhydrous ethanol, perform ultrasonic treatment at a power of 200 W for 16 min to obtain a dispersed system, add aqueous ammonia to the system to adjust the pH to 10, then slowly drop ethyl orthosilicate at a ratio of 1 g of cross-linked starch granules to 2.5 mL of ethyl silicate, react at a constant temperature of 42° C. with stirring for 9 h, then adjust the pH to 7, centrifuge and collect the precipitated product, wash the product alternately with ethanol and deionized water for 3 times, and then vacuum dry the product at 55° C. for 20 h to obtain a coating of silica-coated cross-linked starch gel.

[0086] S4. Take the coating and the preservative base material and mix them evenly in proportion (control the volume proportion of the coating in the metal preservative to be 30%) to obtain the high-efficiency corrosion-inhibiting metal preservative.

[0087] Comparative Example 2

[0088] A highly efficient corrosion-inhibiting metal preservative, the metal preservative comprising a preservative base material and core-shell microspheres dispersed in the preservative base material, wherein the core-shell microspheres are a core-shell structure with a cross-linked starch gel as a core and a modified silicon dioxide coating layer as an outer shell;

[0089] Wherein, in terms of weight, the components of the preservative base material include:

[0090] Component A: 55 parts of bisphenol A epoxy resin, 8 parts of phenyl glycidyl ether, 6 parts of talc, 6 parts of alumina powder, 1 part of sodium dodecyl sulfate, and 1 part of polydimethylsiloxane;

[0091] Component B: 25 parts of polyamide curing agent and 6 parts of propylene oxide butyl ether.

[0092] The preparation method of the high-efficiency corrosion-inhibiting metal preservative comprises the following steps:

[0093] S1. Take bisphenol A epoxy resin and phenyl glycidyl ether and add them to the reactor, stir at 600 rpm for 10 minutes to form a premixed liquid, add sodium dodecyl sulfate to the premixed liquid, continue stirring for 4 minutes, then slowly add talcum powder and alumina powder, and heat to 50°C, maintain stirring for 30 minutes, then add polydimethylsiloxane, stir for 6 minutes to obtain a mixture, and finally grind the mixture with a sand mill to a fineness of ≤50nm to obtain component A; mix the polyamide curing agent with propylene oxide butyl ether, stir at 400 rpm for 18 minutes until homogeneous, to obtain component B.

[0094] S2. Disperse high-amylose corn starch in deionized water at a ratio of 8 g high-amylose corn starch to 100 mL deionized water, stir in a water bath at 82° C. for 35 min to form a transparent starch paste, centrifuge and discard the supernatant, wash with deionized water for 3 times, and vacuum dry at 55° C. for 12 h to obtain starch granules.

[0095] S3. Disperse the starch granules in anhydrous ethanol at a ratio of 1 g starch granules to 90 mL anhydrous ethanol, perform ultrasonic treatment at a power of 200 W for 16 min to obtain a dispersed system, add aqueous ammonia to the system to adjust the pH to 10, slowly drop ethyl orthosilicate at a ratio of 1 g cross-linked starch granules to 2.5 mL ethyl silicate, react at a constant temperature of 42° C. with stirring for 9 h, adjust the pH to 7, centrifuge and collect the precipitated product, wash the product alternately with ethanol and deionized water for 3 times, and then vacuum dry the product at 55° C. for 20 h to obtain a coating of silica-coated cross-linked starch gel.

[0096] S4, add isobutyl triethoxysilane to an ethanol solution with 18 times the mass and a volume concentration of 90%, then add acetic acid to adjust the pH to 4.5, stir well to obtain a treatment solution, then take the coating body and add it to the treatment solution, control the mass ratio of the coating body to isobutyl triethoxysilane to be 8:1, then pass nitrogen protection, stir at a constant temperature of 55°C for 8h, cool to room temperature, add excess ethanol to dilute, and finally centrifuge to collect particles, and wash them alternately with ethanol and deionized water for 3 times, and vacuum dry them at 60°C for 13h, so as to obtain core-shell microspheres with cross-linked starch gel as the core and modified silica coating as the shell. Scanning electron microscopy (SEM) detection shows that the thickness of the modified silica coating is between 76-80nm.

[0097] S5. Take the core-shell microspheres and the preservative base material and mix them evenly according to a certain proportion (control the volume proportion of the core-shell microspheres in the metal preservative to be 30%) to obtain the high-efficiency corrosion-inhibiting metal preservative.

[0098] In addition, on the basis of Example 2, all other step parameters are controlled unchanged, and the thickness of the coating layer of the obtained coating body is changed by adjusting the amount of tetraethyl orthosilicate and the reaction time in step S3 (the thickness of the modified silica coating layer of the core-shell microspheres after surface modification is also detected), and comparative examples 3-6 are obtained, specifically referring to the following Table 1:

[0099] Table 1: Parameter adjustment of comparative examples 3-6 and thickness of final modified silica coating layer

[0100]

[0101]

[0102] 3. Performance Test

[0103] (1) Take several iron sheets of 10 cm × 10 cm × 0.2 cm, remove the oil and rust on the surface of the iron sheets with ethanol, and perform sandblasting: Sa2.5 level (ISO 8501), roughness 40-70 μm, to enhance adhesion, and then dry at 80°C for 10 min.

[0104] (2) Take the high-efficiency corrosion-inhibiting metal preservative samples prepared in Examples 1-3 and Comparative Examples 1-6 respectively, mix the component A and component B of each preservative sample, stir mechanically at 800 rpm for 5 minutes, and then let it stand for 5 minutes to defoam.

[0105] (3) Each preservative sample was sprayed onto the outer surface of the iron sheet by spraying, and the spraying thickness was controlled to be 200 μm. The sample was then baked at 60° C. for 2 h to completely cure the preservative film layer.

[0106] (4) After curing, each iron sheet was rapidly exposed alternately between high temperature (100°C) and low temperature (-20°C) to induce cracks using the thermal expansion and contraction effect. This resulted in multiple obvious cracks (more than 5 cracks and a width greater than 0.1 mm) appearing on the film layer of each iron sheet, and a number of specimens were obtained from each experimental group.

[0107] (5) Take the sample of step (4), remove the coating on one side of the crack along the crack of the sample surface by mechanical scraping, pay attention to retain the complete cross section of the crack, and make the cross section exposed, then use a scanning electron microscope (SEM) to observe the morphology of the crack cross section, obtain a SEM image, and then use a threshold segmentation method to convert the SEM image into a binary image (respectively highlighting the core-shell microsphere area and the base material area), and then use ImageJ software to calculate the total area ratio of the core-shell microsphere area. Five crack sections were taken from each experimental group sample, and the average value was calculated, and the following Table 2 was obtained by statistics.

[0108] (6) Take the sample of step (4), place it indoors (temperature 25°C, humidity 60%) for 2 hours, and refer to the test standard GB-T 1771-2007 "Determination of neutral salt spray resistance of paints and varnishes", and perform a neutral salt spray test (5% NaCl) on each sample. When bubbling, shedding or rusting occurs on the surface of the sample, the test is terminated, and the test duration (i.e., corrosion resistance duration) is recorded. Five samples are taken from each experimental group, and the average value is calculated, and the following Table 3 is obtained by statistics.

[0109] 4. Results Analysis

[0110] Table 2: Results of the total area ratio of core-shell microspheres in the crack section of each experimental group

[0111]

[0112] Table 3: Neutral salt spray test results of each experimental group

[0113]

[0114] It can be seen from Table 2 above that the total area of ​​the core-shell microspheres in the crack section of the samples measured in Examples 1-3 of the present invention is basically the same, reaching 45.7%, 46.1% and 45.8% respectively. The reason is that the different thicknesses of the modified silica shells affect the crack direction and weaken the influence of different actual volume proportions, but Examples 1-3 are significantly higher than the actual volume proportions of 28%, 30% and 32%, respectively. This shows that the present invention uses core-shell microspheres with a specific shell thickness, combined with a surface modification operation, which can make the crack direction pass through the core-shell microspheres as much as possible, so that enough disintegrated core-shell microspheres appear in the cracks. Comparative Examples 1-6 are all adjusted on the basis of Example 2, among which: Comparative Example 1 does not perform the isobutyltriethoxysilane surface modification step, which reduces the bonding strength between the core-shell microspheres and the base material, affects the disintegration of the core-shell microspheres, and the area ratio is significantly reduced to 38.5%; Comparative Example 2 changes the core material, which has no obvious effect here; Comparative Examples 3 and 4 reduce the thickness of the modified silica coating layer of the core-shell microspheres, but the area ratio of the microspheres in the crack section is not significantly improved, indicating that it is meaningless to further reduce the thickness after it is lower than 70-75nm; Comparative Examples 5 and 6 increase the thickness of the modified silica coating layer of the core-shell microspheres. It can be seen that the area ratio of the microspheres in the crack section has decreased significantly, and Comparative Example 6 is even lower than 30% of the actual volume ratio.

[0115] As can be seen from Table 3 above, the samples measured in Examples 1-3 of the present invention all performed outstandingly in the neutral salt spray test results, especially Example 2, where the salt spray resistance time reached 1134h, which was 10.5% and 9.1% higher than that of Example 1 and Example 2, respectively. Comparative Examples 1-6 were all adjusted on the basis of Example 2, where: Comparative Example 1 did not perform the isobutyltriethoxysilane surface modification step, which reduced the bonding strength between the core-shell microspheres and the base material, affecting the disintegration of the core-shell microspheres, and the salt spray resistance time was significantly reduced to 743h; Comparative Example 2 changed the core material and used high-amylose corn starch gelatinized particles without cross-linking modification, which reduced the swelling effect of the core and the structural stability after swelling, resulting in a significant reduction in the salt spray resistance time to 626h; Comparative Examples 3 and 4 reduced The thickness of the modified silica coating layer of the core-shell microspheres was reduced, and the proportion of the microsphere area in the crack section was not improved. However, due to the too low shell thickness, the mechanical strength of the core-shell structure decreased, and breakage occurred during the production and film forming process, affecting the stability of the film layer, resulting in a significant decrease in the salt spray resistance time; Comparative Examples 5 and 6 increased the thickness of the modified silica coating layer of the core-shell microspheres. It can be seen that the excessive shell thickness seriously affected the disintegration of the core-shell microspheres, which in turn resulted in less release of the core material, insufficient gap sealing, and a significant decrease in the salt spray resistance time.

[0116] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A highly efficient corrosion-inhibiting metal preservative, characterized in that: The metal preservative is composed of a preservative base material and core-shell microspheres dispersed in the preservative base material, wherein the core-shell microspheres are a core-shell structure with a cross-linked starch gel as a core and a modified silica coating layer as an outer shell, and the thickness of the modified silica coating layer is 70-86nm; The core-shell microspheres are used to disintegrate along with cracks when cracks appear in the film layer formed by the metal preservative, so as to release the internal cross-linked starch gel, so that the cross-linked starch gel absorbs moisture and expands to seal the cracks.

2. A highly efficient corrosion-inhibiting metal preservative according to claim 1, characterized in that: In terms of weight, the components of the preservative base material include: Component A: 50-60 parts of bisphenol A epoxy resin, 5-10 parts of phenyl glycidyl ether, 2-10 parts of talc, 2-10 parts of alumina powder, 0.5-2 parts of sodium dodecyl sulfonate, and 0.5-1.5 parts of polydimethylsiloxane; Component B: 20-30 parts of polyamide curing agent and 4-8 parts of propylene oxide butyl ether.

3. A highly efficient corrosion-inhibiting metal preservative according to claim 1, characterized in that: The volume proportion of the core-shell microspheres in the metal preservative is 28-32%.

4. A highly efficient corrosion-inhibiting metal preservative according to claim 1, characterized in that: The cross-linked starch gel is prepared by cross-linking and modifying high-amylose corn starch with sodium trimetaphosphate.

5. A highly efficient corrosion-inhibiting metal preservative according to claim 1, characterized in that: The modified silicon dioxide coating layer is obtained by surface modification of the core-shell microspheres by isobutyltriethoxysilane.

6. A highly efficient corrosion-inhibiting metal preservative according to claim 1, characterized in that: The thickness of the modified silicon dioxide coating layer is 76-80 nm.

7. A method for preparing a highly efficient corrosion-inhibiting metal preservative according to any one of claims 1 to 6, characterized in that the steps include: S1. Prepare preservative base material for standby use; S2, preparing cross-linked starch granules for later use; S3, according to the dosage ratio of 1g cross-linked starch particles: 80-100mL anhydrous ethanol, the cross-linked starch particles are dispersed in anhydrous ethanol, and an ultrasonic treatment is performed with a power of 180-220W for 15-18min to obtain a dispersed system, ammonia water is added to the system to adjust the pH to 10-11, and then ethyl orthosilicate is slowly added dropwise according to the dosage ratio of 1g cross-linked starch particles: 2-3mL ethyl silicate, and the reaction is stirred at a constant temperature of 40-45°C for 6-12h, and then the pH is adjusted to 7, centrifuged and the precipitated product is collected, and the product is washed alternately with ethanol and deionized water for 3-4 times, and then the product is vacuum dried at 50-60°C for 18-24h to obtain a coating body of a cross-linked starch gel coated with silica; S4, taking the coating body, and using isobutyltriethoxysilane to modify its surface to obtain core-shell microspheres with cross-linked starch gel as the core and modified silica coating layer as the shell; S5. Take the core-shell microspheres and the preservative base material and mix them evenly according to a certain proportion to obtain the highly efficient corrosion-inhibiting metal preservative.

8. The method for preparing a highly efficient corrosion-inhibiting metal preservative according to claim 7, characterized in that: The specific operations of step S1 are: Take bisphenol A epoxy resin and phenyl glycidyl ether and add them to a reaction kettle, stir at 500-800 rpm for 8-12 minutes to form a premixed liquid, add sodium dodecyl sulfate to the premixed liquid, continue stirring for 3-5 minutes, then slowly add talcum powder and alumina powder, and heat to 45-55° C., maintain stirring for 25-35 minutes, then add polydimethylsiloxane, stir for 4-8 minutes to obtain a mixture, and finally grind the mixture with a sand mill to a fineness of ≤50nm to obtain component A; The polyamide curing agent and propylene oxide butyl ether are mixed, and stirred at 300-500 rpm for 15-20 minutes until homogeneous, to obtain component B.

9. The method for preparing a highly efficient corrosion-inhibiting metal preservative according to claim 7, characterized in that: The specific operation of step S2 is as follows: according to the dosage ratio of 5-10g high-amylose corn starch: 100mL deionized water, the high-amylose corn starch is dispersed in deionized water, stirred in a water bath at 80-85°C for 30-40min to form a transparent starch paste, and then sodium trimetaphosphate accounting for 3-8% of the mass of starch is added thereto, the pH is adjusted to 9-11 with NaOH solution, the temperature is raised to 50-60°C, and the reaction is stirred for 2-4h to form a cross-linked starch gel. After the reaction solution is cooled, the supernatant is discarded by centrifugation, and then washed with deionized water 3-4 times, and vacuum dried at 50-60°C for 10-15h to obtain cross-linked starch granules.

10. The method for preparing a highly efficient corrosion-inhibiting metal preservative according to claim 7, characterized in that: The specific operation of step S4 is as follows: adding isobutyl triethoxysilane to an ethanol solution with a mass of 15-20 times and a volume concentration of 90%, then dropping acetic acid to adjust the pH to 4-5, stirring thoroughly to obtain a treatment liquid, then adding the coating body to the treatment liquid, controlling the mass ratio of the coating body to isobutyl triethoxysilane to be 5-10:1, then introducing nitrogen protection, stirring at a constant temperature of 50-60°C for 6-12h, cooling to room temperature, adding excess ethanol to dilute, and finally centrifuging to collect the particles, and washing them alternately with ethanol and deionized water for 3-4 times, and vacuum drying at 55-60°C for 12-15h to obtain core-shell microspheres with a cross-linked starch gel as the core and a modified silica coating layer as the shell.